Estimating the Marginal Rate of Substitution in the Intertemporal Capital Asset Pricing Model - Scott, Louis O. (The Review of Economics and Statistics, 1989)
A method for estimating the marginal rate of substitution in the intertemporal capital asset pricing model is presented. The marginal rate of substitution is treated as an unobservable and one-period returns are used to develop a method of moments estimator that is consistent. Consistency depends on both a large number of time observations and a large number of securities. In the last section of the paper, the estimates of the marginal rate of substitution are used to test whether stock prices are unbiased predictors of ex post market fundamentals. Copyright 1989 by MIT Press.